2014
DOI: 10.1097/md.0000000000000194
|View full text |Cite|
|
Sign up to set email alerts
|

Hepatic Angiomyolipoma Mimicking Hepatocellular Carcinoma

Abstract: Hepatic angiomyolipoma (HAML) is a rare mesenchymal tumor of the liver with marked histological diversity. The present study was to review the magnetic resonance imaging (MRI) and clinical pathological features of HAML resembling hepatocellular carcinoma (HCC).Nine patients who underwent surgical resection and had pathological diagnosis of HAML were retrospectively analyzed.All of 9 patients (5 males and 4 females) had a solitary hepatic mass with a median size of 4 cm (from 1.4 cm to 15.3 cm). Seven cases wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…Because the radiological features of HAML depend on the relative proportion of adipose cells in the tumor, HAML was not readily distinguishable from HCC [ 5 8 ]. Liver biopsy was helpful in the preoperative diagnosis of AML [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the radiological features of HAML depend on the relative proportion of adipose cells in the tumor, HAML was not readily distinguishable from HCC [ 5 8 ]. Liver biopsy was helpful in the preoperative diagnosis of AML [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, HAML lesions identified by focusing on gadolinium ethoxybenzyl diethylenetriamine pentaacetic acid-enhanced magnetic resonance imaging (Gd-EOB-DTPA MRI), immunohistochemistry, and both clinical and pathological characteristics of the tumors were reported [ 5 ]. However, to the best of our knowledge, there is no case report to date on the combination of Gd-EOB-DTPA MRI, immunohistochemistry, and electron microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis of PEComas is, however, problematic. In a previous study, 9 patients incidentally identified as having asymptomatic liver tumors were preoperatively diagnosed on the basis of MRI and their clinical features as 6 hepatocellular carcinomas, 2 adenocarcinomas, and 1 AML [8]. In the current case, the tumor was initially considered an intrahepatic cholangiocarcinoma because of an obstruction of the B2 bile duct and dilatation of its periphery.…”
Section: Discussionmentioning
confidence: 99%
“…MRI scan was performed by a GE Signa HDx 1.5T scanner or a GE Signa HDx 3.0T scanner (both from GE Healthcare, Milwaukee, WI, USA). The scans followed the protocol for standard contrast-enhanced abdominal CT or MRI examination as previously described 8 9 10 . The slice thickness was 1.25 mm, 2.5 mm, 5 mm, and 7 mm, respectively, for determining the effects of slice thickness on the recognition of VTSS and was 5 mm for both CT and MRI in other analysis.…”
Section: Methodsmentioning
confidence: 99%